The Impact of the Characteristics of Local Governments and the Results of BPK Audits on the Performance of Governance in Papua and West Papua - Adolf Z. D. Siahay; Rezianof R. Siahay (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This research aims to empirically test the effect of the characteristics of local government, namely regional size, regional wealth, fiscal dependence, and regional spending, as well as the results of BPK audits including audit findings and audit opinions on the performance of local government administration in Papua and West Papua provinces. This research used data from 40 eligible regencies/cities in those provinces out of 42. According to the results of the findings, each indicator measuring local government characteristics was measured through the ratio of fixed assets to total assets, the ratio of locally generated revenue (PAD) to total regional income, the ratio of balancing funds to total regional income, in addition to capital expenditure-to-total regional expenditure ratio, significantly affected the performance of local government administration, as did audit results from the BPK; which in this case are assessed through the ratio of BPK findings against the total regional expenditures, as well as audit opinions on a four-point scale. Regional wealth, fiscal dependence, and audit opinions all have a positive and significant impact on local government performance. In contrast, regional size and regional expenditure, which were expected to exert a positive impact, have a negative but statistically non-significant effect. Audit findings also show a negative impact, but this relationship is statistically insignificant. This study contributes to the understanding of the financial and audit-related variables affecting governance performance in the context of Papua and West Papua.